h - Satiric Literature and Other “Popular” Literary Genres in Egypt Today - Jacquemond, Richard (Journal of Arabic and Islamic Studies, 2017)
This article starts by describing some characteristics of current Egyptian popular literature, based on field observation at the Cairo 2016 book fair and a survey of the Egyptian authors available on the social network Goodreads, and puts the stress on the spectacular rejuvenation this market experienced in the last ten years. It focuses then on one of this market’s main genres, namely, satiric literature, and suggests through the analysis of various authors’ trajectories and works that it reveals a tension between reformism and subversion, a tension similar to the one that characterises the predicament of the Egyptian intelligentsia in the post-2011 context. Key words: Egypt, readership, bestsellers, satire, youth, reformism, subversion